Perancangan User Experience Aplikasi Mobile e-Lelang menggunakan Metode Human Centered Design - Beril Sanda; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The auction buying and selling process involves bidding goods to bidders and bidders offering higher prices until the goods are sold at the highest agreed price. Recently, internet technology has begun to be used to carry out the auction process. Even so, the online auction process still encounters several problems such as misinformation, differences in product expectations, fraud, and errors in pricing. To overcome these problems, developing auction applications can help minimize these obstacles. It is essential to strike a balance between an attractive interface design and a pleasant user experience. The purpose of this research is to design an interface and user experience for online media auctions using the Human Centered Design method. This method engages potential users and includes creating personas, empathy maps, and information architecture to identify user needs. Next, the implementation process is carried out through the creation of wireframes, wireflows, mockups, and prototypes to carry out usability tests and system usability scale tests. The test results show that the implementation has reached 95% effectiveness, and 92.09% efficiency, and the user satisfaction level reaches 77.19 on the SUS scale which is above the average. It can be concluded that the solution design created can minimize the problems that exist in the online auction process.